Control strategies for gutter maintenance robot - Hernandez, Marllely; Dussan, Sofia; Chavarro, Adrian; Rodriguez, Ruthber; Arbulu, Mario (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This paper presents the control system of the ROMANCAN robot (Gutter Maintenance Robot), a tracked differential mobile robot designed to clean buildings gutters and reduce the risk of operators falling. The focus on the control system deals with following wall, to correct the robot trajectory in real time. In addition, the integrated electronic components, such as sensors and actuators, are detailed. The simulation results and experimental tests, show the effectiveness of the system in simulated conditions, and with physical prototype, it is noticed at kinematic control that the compensation angle can be computed by dividing 2.5 the initial robot deviation angle; otherwise the dynamic control allows compensate additional real environment disturbs contributing to the field of mobile robotics and automation in narrow spaces at urban environments.